1992
DOI: 10.1016/0035-9203(92)90328-a
|View full text |Cite
|
Sign up to set email alerts
|

Causes of conjunctivitis and keratoconjunctivitis in Karachi, Pakistan

Abstract: The causes of conjunctivitis and keratoconjunctivitis in 388 patients who attended eye casualty departments in Karachi, Pakistan, during a 5 month period were investigated. Most of these infections were diagnosed as adenovirus (291, 75%) or bacterial (71, 18.3%). Of the remainder, 9 cases (2.3%) were caused by herpes simplex virus and 7 (1.8%) by Chalmydia trachomatis. There was no evidence of typical active trachoma in this urban population. Bacteria or Candida albicans were also grown from 44 of the adenovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 13 publications
2
50
1
1
Order By: Relevance
“…In this study, the positive rate of HAdV was 42.23z, which is consistent with the prevalence of 49z throughout East Asia in the 1980s (24). However, the prevalence of HAdV in this study was lower than that reported in Japan during 2005-2006 (82z) (25) and Pakistan (75z) (26), whereas there was a much lower prevalence in other countries, such as the USA (17.16z) (27) and Mexico (24.39z) (28). It is well known that CA24v is highly contagious, especially due to the incredible mobility of populations worldwide (29).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the positive rate of HAdV was 42.23z, which is consistent with the prevalence of 49z throughout East Asia in the 1980s (24). However, the prevalence of HAdV in this study was lower than that reported in Japan during 2005-2006 (82z) (25) and Pakistan (75z) (26), whereas there was a much lower prevalence in other countries, such as the USA (17.16z) (27) and Mexico (24.39z) (28). It is well known that CA24v is highly contagious, especially due to the incredible mobility of populations worldwide (29).…”
Section: Discussionsupporting
confidence: 88%
“…Approximately 20z-70z (3-5) of infectious conjunctivitis is thought to be of viral etiology, which has been reported to account for 8z-75z of acute cases (6)(7)(8). Several previous studies have reported that approximately 65z-90z of viral conjunctivitis cases in Japan and Pakistan in the 19th and 20th centuries were caused by human adenocirus (HAdV) (8)(9)(10). Herpes simplex virus (HSV) is regarded as the leading infectious cause of corneal blindness among developed nations (11).…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviruses were found in the majority of the cases examined (66%); among them, Ad8 was the most common. These results are in agreement with those obtained in Karachi, Pakistan, where adenoviruses were isolated in 75% of patients with acute follicular conjunctivitis [Woodland et al, 1992]. Nine isolates were recognized by PCR-RFLP as Ad8.…”
Section: Discussionsupporting
confidence: 93%
“…Adenoviruses have been found to be the most common cause of infectious conjunctivitis in humans (Ishii et al, 1987;Woodland et al, 1992). With the advent of improved antemortem diagnostics, a marked increase in diagnoses of human adenoviral disease has occurred (Rocholl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%